Catalytic micro-ozonation by Fe3O4 nanoparticles @ cow-dung ash for advanced treatment of biologically pre-treated leachate. (January 2019) - Ma, Cui; Yuan, Pengfei; Jia, Shengyong; Liu, Yaqi; Zhang, Xingjun; Hou, Sen; Zhang, Hanxu; He, Zhengguang
Highlights: Nano-Fe3 O4 @cow-dung ash was prepared by in situ precipitation oxidization method. The organics removal and biodegradability were both significantly improved. It was demonstrated as a promising catalyst for catalytic micro-ozonation process. Abstract: In this work, the biologically pre-treated leachate was subjected to catalytic micro-ozonation using cow-dung ash composites loaded with Fe3 O4 nanoparticles (nano-Fe3 O4 @CDA) as the catalyst. The optimal conditions used were nano-Fe3 O4 @CDA dosage of 0.8 g/L, input ozone of 3.0 g/L, and reaction time of 120 min. This environment yielded the following results: The COD and color number (CN) removal reached 53% and 89%, respectively, and the BOD5 /COD increased from 0.05 to 0.32. The catalytic micro-ozonation partially degraded the refractory substances into intermediates with lower molecular weight. The percentage of phenolic compounds decreased sharply from 28.08% to 8.56%, largely due to the opening of the ring as well as to the formation of organic intermediates with a low molecular weight. Based on the results culled from the electron paramagnetic resonance (EPR), it is evident that the nano-Fe3 O4 @CDA catalyst can accelerate in order to generate OH. This was the main mechanism involved in its excellent ability to degrade refractory pollutants. These results demonstrated the potential use of nano-Fe3 O4 @CDA as a catalyst in the catalytic micro-ozonation process.